2021
DOI: 10.1007/s00526-021-01959-x
|View full text |Cite
|
Sign up to set email alerts
|

Global higher integrability for minimisers of convex functionals with (p,q)-growth

Abstract: We prove global $$W^{1,q}({\varOmega },{\mathbb {R}}^m)$$ W 1 , q ( Ω , R m … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 84 publications
(129 reference statements)
0
8
0
Order By: Relevance
“…recalling the bounds (29), (44), ( 46), (48), (57) we are led to the lower bound for the exponent . Assuming the validity of (58) and returning to (43) we now have shown that for i sufficiently close to −1∕2 the right-hand side of (43) can be splitted into terms which either can be absorbed in the left-hand side of (43) or stay uniformly bounded, hence for a finite constant c independent of m. Passing to the limit m → ∞ in (59) our claim (11) follows. Obviously ( 12) is a consequence of (58) and the definition of (55)…”
Section: This Gives ( ε ≪ 𝜀)mentioning
confidence: 66%
See 2 more Smart Citations
“…recalling the bounds (29), (44), ( 46), (48), (57) we are led to the lower bound for the exponent . Assuming the validity of (58) and returning to (43) we now have shown that for i sufficiently close to −1∕2 the right-hand side of (43) can be splitted into terms which either can be absorbed in the left-hand side of (43) or stay uniformly bounded, hence for a finite constant c independent of m. Passing to the limit m → ∞ in (59) our claim (11) follows. Obviously ( 12) is a consequence of (58) and the definition of (55)…”
Section: This Gives ( ε ≪ 𝜀)mentioning
confidence: 66%
“…Even more recently the contribution of Koch [11] addresses the global higher integrability of the gradient of solutions of variational problems with (p, q)-growth, which to our knowledge is the first result to improve global integrabilty of the gradient allowing full anisotropy with different growth rates with respect to different partial derivatives. The boundary data are supposed to belong to some fractional order spaces (see, e.g., [12] or [13]) and roughly speaking are handled like an additional x-dependence following ideas as outlined in, e.g., [14] for the interior situation.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The reverse question is considerably more difficult and the answer is delicate already in the case of convex, real-valued integrands satisfying p-growth. We do not discuss the issue of integrands with (p, q)-growth further here but refer to [23,12,18,19,20,13,14] for further discussion and references. The question for convex integrands without growth conditions has been studied in [6].…”
Section: Introduction and Resultsmentioning
confidence: 99%
“…Currently, regularity theory for non-autonomous integrands with non-standard growth, e.g. p(x)-Laplacian or double phase functionals, are a very active field of research, see, e.g., the recent papers [4,9,12,18,16,17,19,20,21,23,28,27,30,35] and [2,11] for related results about the Lavrentiev phenomena.…”
mentioning
confidence: 99%